PENGARUH GAYA KEPEMIMPINAN DAN STANDAR OPERASIONAL PROSEDUR (SOP) TERHADAP KINERJA PEGAWAI CV. GHIVARI PERDANA KOTA BATAM, KEPULAUAN RIAU - Sandy Perdana, Andra; Givari, Shafwan Haikal; Erina, Theeresya; Piariska, Suci; Zikry, Khairulah (LPPM Universitas Ibnu Sina, 2026)
The aim of this research is to evaluate the impact of leadership style and Standard Operating Procedures (SOP) on employee performance. From the research references carried out, researchers can conclude that the variables of leadership style and Standard Operating Procedures have a significant influence on employee performance partially and simultaneously. This shows that leadership style and standard operational procedures are important factors in improving employee performance at CV. Prime Ghivari. Implementing a good leadership style and accurate SOPs can improve employee performance significantly. The f test shows the calculated f value is 55,813, greater than the f table, namely 10,925, with a significance level of 0.000, smaller than 0.05. From this situation, it can be concluded that both leadership style (X1) and Standard Operating Procedures (SOP) (X2) simultaneously influence employee performance (Y).